Penerapan Media Evaluasi Berbasis Wordwall Pada Mata Pelajaran Pendidikan Agama Islam Kelas IX di SMP - Mutmainnah; Annisa Fadhilah; Suci Wahdaniya; Dhia Azizah Faisal (South Sulawesi Education Development, 2024)
The development of learning technology today is still not much used by educators in schools in dealing with the problems faced. The research is aimed at applying wordwall media to improve the discipline of students. This research is a kind of classroom action study involving 17 pupils. The data was collected using observation sheets and validation sheet analysed through quantitative descriptive to determine the improvement of data between cycles. The results of the study showed media expert validation of 75% and of material expert of 100% so obtained final validation with 87.5% of categories very valid. Between cycle I and cycle II the research found a rather significant improvement namely cycles I by 47% and 70% in cycles II, thus achieving the standard of research success in improving discipline and it was concluded that the application of wordwall media can improve the discipline of pupils especially in class IX B middle school 5 Palopo State.